Delinquency, careers, and prospects: a conceptual paper - Ghazali, Mohd Al'Ikhsan; Md Sawari, Siti Salwa; Abdullah, Naimatul Azkiyai (2018)
Legal opinion to protect the society and juvenile offenders is important from social aspect. Bad boy or bad girl labelled towards the juvenile in the rehabilitation centre should be scrapped because it is tantamount to killing the hopes and indirectly makes them thinking that they are useless. The ultimate outcome of this vicious cycle may trap them in constant negativity and poverty even for their entire lifetime, unemployment and periodic incarceration, dependency for substance abuse, and failure to maintain societal norms. The purposes of this study is to review planning and career prospects for juvenile and develop a model for the future of juvenile delinquency career. Methods of quantitative and qualitative studies will be used in the study. All survey data will be analyzed using the Statistical Package for the Social Science (IBM SPSS) software, while the interviews will be analyzed using Nvivo